Field Test and Numerical Research of Blast-Induced Liquefaction in Calcareous Sand - Changchun Li; Yumin Chen; Yingkang Yao; Yonggang Gou; Qiongting Wang; Junwei Guo; Xiao Xie (Shock and Vibration)
In recent years, the engineering losses caused by liquefaction of calcareous sand foundations have gradually increased. However, there are relatively few studies on the mechanism of blast-induced liquefaction in saturated calcareous sand foundations. In order to analyze the mechanism of blast-induced liquefaction in saturated calcareous sand foundations, we study the variation of the excess pore water pressure ratio at different scaled distances by field tests and the LS-DYNA software. The results show that based on the field test results, due to the characteristics of the calcareous sand itself being broken, the excess pore water pressure ratio of the calcareous sand foundation at the same scaled distance is smaller than that of the quartz sand foundation. The effectiveness of the Arbitrary Lagrangian Eulerian (ALE) algorithm is verified based on the field test results, and the pore water pressure response in saturated calcareous sand foundations under different TNT equivalents is further analyzed. The excess pore pressure ratio response gradually decreases with the increase of scaled distance. When the scaled distance is less than 1.856 m/kg1/3, a complete liquefaction phenomenon will occur. The empirical prediction formula for single explosive blast-induced liquefaction in saturated calcareous sand foundations is derived. The research results can provide a theoretical reference for the prediction of blast-induced liquefaction in saturated calcareous sand foundations.